Structural characteristics of 3C–SiC thin films grown on Si-face and C-face 4H–SiC substrates by high temperature chemical vapor deposition. (January 2023) - Feng, Zhe Chuan; Lin, Hao-Hsiung; Xin, Bin; Tsai, Shi-Jane; Saravade, Vishal; Yiin, Jeffrey; Klein, Benjamin; Ferguson, Ian T.
Abstract: Hetero-epitaxy of 3C–SiC on Si-face and C-face 4H–SiC is experimentally investigated and corresponding growth model is identified. This study of polytypes of SiC will be useful for band-gap engineering, optical, electrical, and electronic applications of SiC. 3C–SiC was epitaxially deposited on 4H–SiC using a high temperature chemical vapor deposition. The primary factor affecting the epi-quality on Si-face SiC is double positioning boundary (DPB) defect. An adatom migration model elucidates the formation of the V-shaped DPB defect structures. On C-terminated 4H–SiC, super-V-shaped-structure (SVSS) defects and polycrystalline complexes in 3C–SiC are formed. These characteristics of 3C–SiC are measured and analyzed using transmission electron microscopy, X-ray diffraction, atomic force microscopy, and scanning electron microscopy techniques. A model considering adatoms' migration in step-flow direction and anti-step-flow direction explains the SVSS defects. Effects of both step-flow and anti-step-flow growth mode on the atom adsorption near the step edge are discussed. Highlights: 3C–SiC films on Si- and C-face 4H–SiC grown by high temperature chemical vapor deposition. Penetrating characterization using TEM, XRD, AFM, SEM, and analyses. Double positioning boundary, Super-V-shaped-structure and polycrystalline complexes defects investigated in depth. Atomic-structure model proposed to demonstrate the observed twinning structure. Modeling adatoms' migration in step-flow/anti-step-flow demonstrated Super-V-shaped-structure defects.